THE FRAGILITY OF THE DIRECT ELECTION SYSTEM FROM THE PERSPECTIVE OF PANCASILA SEMANTICS - Muhammad Hasan Abdillah; Iskandarsyah Siregar; Awang Azman bin Awang Pawi (Journal of Social Political Sciences, 2025)
With the Pancasila concept as a semantic frame, this report conceives democracy as a discursive system created by language. The research uses an interdisciplinary approach, integrating political theory, linguistics, and cultural analysis. It applies a mixed-method design, combining critical discourse analysis, corpus linguistics, and a quantitative model. The dataset contains about 950,000 words of electoral discussions (2019–26). These include official statements, campaign narratives, news reports, and digital communication. The findings reveal a semantic shift from deliberative language grounded in Pancasila, such as musyawarah and mufakat, to a competitive, evaluative, identity-based rhetorical mode. Competitive lexical items account for 41.7% of all words in the data. The count of deliberative terms drops to 18.6%. There is a strong positive relationship between the intensity of data evaluation and engagement (r = 0.72, p < .001). Qualitative examination shows competing framing, symbolic simplification, and identity polarisation dominate. Elections become a rivalry rather than a collective decision-making process. This semantic change is verified against three provable sources. The first is the nationwide shift from Pancasila scholarship to digital communication, which has heightened its seriousness. The research concludes that the fragility of Indonesia's direct electoral system stems from semantic differences between Pancasila’s deliberative aspect and patterns of public language. To maintain democratic legitimacy, social harmony, and long-term viability, Indonesia's electoral democracy must be adjusted